Starter's guide to Verilog 2001. - Ciletti, Michael D., ....- (Upper Saddle River : Pearson, 2004)
For undergraduate courses in Advanced Digital Logic and Advanced Digital Design in departments of electrical engineering, computer engineering, and computer science. Introducing the Verilog HDL in a brief format, this text presents a selected set of the changes the popular hardware underwent in its first revisionemerging as IEEE Std 1364-2001 or Verilog-2001. It addresses the main features that support the design of combinational and sequential logic, and emphasizes synthesizable models, with a limited discussion of the theoretical framework for synthesis.
Keywords: Logische schakelingen